Pelatihan Pemahaman Konsep Bisnis bagi Siswa Menengah Atas dengan Metode Pendekatan Partisipatif dan Tindakan - Rakhdiny Sustaningrum; Dwinita Laksmidewi; Stefano Capriati Winarno (I-Com: Indonesian Community Journal, 2024)
Entrepreneurship is considered a primary driver of economic growth, as entrepreneurs possess innovative, proactive, and risk-taking spirits. Instilling entrepreneurial character from an early age is crucial in shaping strong mindsets and intentions. Thus, an outreach was conducted using the Participatory Learning and Action (PLA) method in high schools, where students often have limited understanding beyond basic buying and selling concepts. The outreach involved practical activities and interactive discussions, introducing entrepreneurial characteristics, motivation, and elements of the business model canvas. The results indicate an improvement in entrepreneurial understanding, reflected in the creativity of products generated by students, yet there remains a need to enhance entrepreneurial motivation. This outreach underscores the importance of an entrepreneurial approach in education to support economic advancement.